Strategi Kebijakan Pengelolaan Sampah yang Efektif di Dinas Lingkungan Hidup Kota Singkawang - Terry Listiyadi (CV Global Research Publication, 2026)
The high volume of waste managed in 2024, reaching 31,187.09 tons per day, with a waste handling rate of 87.89%, has resulted in an increasing amount of waste being transported to the Wonosari Final Disposal Site (TPA). The purpose of this policy paper is to recommend a Waste Management Policy Strategy for the City of Singkawang. The methods and analytical tools employed in this study include Fishbone Analysis, USG Analysis (Urgency, Seriousness, Growth), the Problem Tree Method, and policy analysis theory as proposed by William N. Dunn. This policy paper identifies several key issues, namely inadequate waste management infrastructure, the absence of effective Standard Operating Procedures (SOPs) for waste management within the Singkawang City Environmental Agency, and low levels of public awareness and participation in waste management practices. The proposed policy alternative is the development of effective Waste Management SOPs for the Singkawang City Environmental Agency. Based on the findings of the analysis, the author recommends that the Head of the Singkawang City Environmental Agency issue a Decree establishing the Waste Management SOPs for the agency.